2013
DOI: 10.1016/s1470-2045(13)70136-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiotherapy with or without cetuximab in patients with oesophageal cancer (SCOPE1): a multicentre, phase 2/3 randomised trial

Abstract: Cancer Research UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
258
3
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(282 citation statements)
references
References 35 publications
11
258
3
10
Order By: Relevance
“…The reasons for this difference could be that trstuzumab is a MoAb specially targeting HER2 and all patients in anti-HER2 subgroup are diagnosed HER2 positive. The decreasing OS in anti-EGFR subgroup may due to the limited clinical trials in gastric and gastroesophageal cancer and in fact some trials in other cancers draw the similar conclusions (Douillard et al, 2010b;Crosby et al, 2013). The PFS was significantly improved in the anti-HER2 subgroup (HR 0.72, 95% CI 0.60-0.84, P<0.05; I 2 =0.0%, p =0.897), but was significantly reduced in anti-EGFR subgroup (HR 1.13, 95% CI 0.98 -1.28, P<0.05).…”
Section: Analysis From Randomized Control Trials Of Chemotherapy Plusmentioning
confidence: 82%
“…The reasons for this difference could be that trstuzumab is a MoAb specially targeting HER2 and all patients in anti-HER2 subgroup are diagnosed HER2 positive. The decreasing OS in anti-EGFR subgroup may due to the limited clinical trials in gastric and gastroesophageal cancer and in fact some trials in other cancers draw the similar conclusions (Douillard et al, 2010b;Crosby et al, 2013). The PFS was significantly improved in the anti-HER2 subgroup (HR 0.72, 95% CI 0.60-0.84, P<0.05; I 2 =0.0%, p =0.897), but was significantly reduced in anti-EGFR subgroup (HR 1.13, 95% CI 0.98 -1.28, P<0.05).…”
Section: Analysis From Randomized Control Trials Of Chemotherapy Plusmentioning
confidence: 82%
“…Similarly, SCOPE1 trials in patients in the UK did not show any benefits to adding cetuximab to a standard chemo-/radiotherapy treatment regimen. However, in a multi- center phase II trial in Chinese patients with non-resectable, locally advanced ESCC, it was found that cetuximab can be safely used concurrently with chemo-and radiotherapy and may actually increase the clinical response rate (18,19). The reasons for these conflicting results of cetuximab combination therapy remain unclear, but recent data point to the influence of mutations in, or amplification of, specific genes; for instance, combination therapy had different survival outcomes for patients depending on the presence of EGFR or MET gene amplifications, or mutations in EGFR, KRAS, or PI3CA (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…This may be the result of a low expression of EGFR and mutation of the K-RAS gene of the tumors investigated in this study (26). Currently it is not clear whether addition of cetuximab to the radio-chemotherapy of esophageal cancer can improve the overall survival of these patients (27,28). In the SCOPE1 trial, treatment included two courses of induction chemotherapy with cisplatin (60 mg/m 2 on day 1) and capecitabine (625 mg/m 2 twice daily on days 1-21) followed by radio-chemotherapy with 50 Gy of radiotherapy plus two concurrent courses of chemotherapy with or without the addition of cetuximab.…”
Section: Definition Of Dose Limiting Toxicities (Dlts)mentioning
confidence: 97%